2020
DOI: 10.3390/ijms21114004
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposites for X-Ray Photodynamic Therapy

Abstract: Photodynamic therapy (PDT) has long been known as an effective method for treating surface cancer tissues. Although this technique is widely used in modern medicine, some novel approaches for deep lying tumors have to be developed. Recently, deeper penetration of X-rays into tissues has been implemented, which is now known as X-ray photodynamic therapy (XPDT). The two methods differ in the photon energy used, thus requiring the use of different types of scintillating nanoparticles. These nanoparticles are know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 84 publications
(95 reference statements)
1
19
0
7
Order By: Relevance
“…As a result, it has been shown that for all samples nanoparticles are in the range of 5-17 nm with predominant fractions of ~10 nm. This fact complies with the requirements for nanophosphors as a part of nanocomposites that can be used in XPDT [35,36]. Thus, according to the obtained particle size distribution, all synthesized nanomaterials are suitable for the subsequent synthesis of nanocomposites for XPDT.…”
Section: Transmission Electron Microscopy (Tem)supporting
confidence: 75%
“…As a result, it has been shown that for all samples nanoparticles are in the range of 5-17 nm with predominant fractions of ~10 nm. This fact complies with the requirements for nanophosphors as a part of nanocomposites that can be used in XPDT [35,36]. Thus, according to the obtained particle size distribution, all synthesized nanomaterials are suitable for the subsequent synthesis of nanocomposites for XPDT.…”
Section: Transmission Electron Microscopy (Tem)supporting
confidence: 75%
“…Band gap materials convert X-rays into light photons in the UV-vis region, which can be used to activate PSs. This is the basis of a combination of PDT and radiation therapy known as X-ray PDT (XPDT) [177,178]. The use of light is one of the limitations of PDT, and the strong tissue penetration of X-rays can compensate for this shortcoming.…”
Section: Radiotherapymentioning
confidence: 99%
“…In this Thematic Area, 56 articles have been published [ 48 , 64 , 104 , 108 , 110 , 124 , 195 , 252 , 253 , 254 , 255 , 256 , 257 , 258 , 259 , 260 , 261 , 262 , 263 , 264 , 265 , 266 , 267 , 268 , 269 , 270 , 271 , 272 , 273 , 274 , 275 , 276 , 277 , 278 , 279 , 280 , 281 , 282 , 283 , 284 , 285 , 286 , 287 , 288 , 289 , 290 , 291 , 292 , 293 , 294 , 295 , 296 , 297 , 298 , 299 , 300 ], an...…”
Section: Articles On the Various Directionsunclassified
“…The processes in inorganic nanomaterials were considered in one way or another, in articles [ 104 , 108 , 110 , 252 , 253 , 264 , 265 , 267 , 268 , 269 , 270 , 275 , 276 , 279 , 281 , 285 , 286 , 287 , 297 ]. Additionally, here, the materials in which these processes are implemented are very diverse.…”
Section: Articles On the Various Directionsmentioning
confidence: 99%